UPAYA MENINGKATKAN HASIL BELAJAR FORHAND DAN BACKHAND BULUTANGKIS MELALUI MODIFIKASI RAKET KAYU PADA SISWA - Ridwan Sudirman; Dedi Aryadi (JURNAL PENDIDIKAN DASAR SETIA BUDHI (JPDS), 2021)
The purpose of this research is to create a modification product of racket modification media from wood to improve forhand and back hand training in badminton games. The research approach used is development research. The results of the study obtained aspect 1 value of "while participating in badminton using a racquet modification media, how do you feel?" Response 84 students or 84% of respondents feel happy. Aspect 2. "Do you use the modification as a towel handle with adhesive, how do you feel?" Response 79 students or 79% of respondents find it easier to learn. 3rd question. "What do you think about the assignment during the learning process?" The response of 83 students or 83% of respondents felt easy, 15 people or 15% of respondents answered mediocre, and 2 people or 2% of respondents answered difficult. The answer to aspect no-4. "What do you think about the modification with glue as a handle?" The response of 86 students or 86% of respondents answered could be continuedThe use of badminton racket grip products has a positive impact on students to learn the technique of racket grip Kata Kun. This research is based on the author's observations in the field, regarding the smash forehand material. The method used is the Action Research method with qualitative and quantitative data collection, namely Class A Morning Semester IV with a total of 36 students, consisting of 31 male students and 5 female students. This research involved Badminton Game Lecturer as a collaborator, the research was conducted in two cycles, each cycle consisting of two meetings. The first cycle activity which was realized through learning the throwing of the ball gave the following results: 1) students did not understand the concept of smash forehand badminton games, for example students still make the forehand smash not by straightening their arms completely, 2) students do not understand how to hold the racket when doing bad forehand smash for badminton, 3) students are not confident when doing smash forehand for badminton. II which is realized through learning to throw the ball above gives the following results: 1) students begin to understand the basic concepts of the smash forehand badminton game, this understanding can be seen from the ara students do and learn the movement of badminton smash forehand games well, 2) students can perform stages of badminton smash forehand blows well, 3) motivation and confidence of students increases when doing badminton forehand smash blows The results of this study an increase in learning outcomes forehand badminton smash through upper ball throwing learning, an increase occurs in each learning that begins with initial observation, cycle I and ends in cycle II. An increase in the psychomotor aspect, students have understood the concept of smashforehand badminton. In the cognitive aspect, students' understanding increases along with the process of following the lessons, it can be seen from the enthusiasm and enthusiasm of students participating in learning, student confidence in interacting with students and lecturers, the value of honesty, discipline, cooperation responsibility and tolerance between students that they show. Keywords: Modification, forhand and back hand training, Badminton Leaning Media. Abstrak Tujuan dari penelitian ini adalah menciptakan produk modifikasi media modifikasi raket dari kayu untuk meningkatkan latihan forhand dan back hand dalam permainan bulutangkis. Pendekatan penelitian yang digunakan adalah penelitian pengembangan. Hasil penelitian diperoleh nilai aspek 1 tentang “selama mengikuti bulutangkis dengan menggunakan media modifikasi alat raket, bagaimana perasaanmu?” Respon 84 siswa atau 84% responden merasa senang. Aspek ke 2. “Apakah penggunaan modifikasi sebagai pegangan handuk dengan perekat, apa yang kamu rasakan?” Respon 79 siswa atau 79% dari responden merasa lebih mudah untuk belajar. Pertanyaan ke-3. “Apa pendapatmu tentang tugas selama proses pembelajaran berlangsung?” Respon 83 siswa atau 83% responden merasa mudah, 15 orang atau 15% responden menjawab biasa-biasa saja, dan 2 orang atau 2% dari responden menjawab sulit. Jawaban untuk aspek no-4. “Apa pendapat anda tentang modifikasi dengan perekat sebagai pegangan “respon 86 siswa atau 86% responden menjawab bisa diteruskan. Penggunaan produk pegangan raket bulutangkis memberikan dampak positif pada mahasiswa untuk belajar teknik pegangan raket Kata KunPenelitian ini dilator belakangi oleh hasil pengamatan penulis dilapangan, mengenai materi smash forehand.Untuk itu, penelitian ini bertujuan untuk meningkatkan hasil belajar terhadap pukulan smash forehanddalam permainan bulutangkis melalui pembelajaran. Metode yang digunakan adalah metode penelitian tindakan (Action Research) dengan pengambilan data kualitatif dan kuantitatif yaitu kelas A Pagi Semester IV dengan jumlah Mahasiswa sebanyak 36 mahasiswa, yang terdiri dari 31 mahasiswa laki-laki dan 5 mahasiswa perempuan. Penelitian ini melibatkan Dosen Mata Kuliah Permaianan Bulutangkis sebagai kolaborator, penelitian dilakukan sebanyak II siklus, setiap siklus terdiri dari dua kali pertemuan.Kegiatan siklus I yang direalisasikan melalui pembelajaran lempar bola atas memberikan hasil sebagai berikut: 1) mahasiswa belum paham akan konsep pukulan smash forehand permainan bulutangkis, contohnya mahasiswa masih melakukan gerakan pukulan smash forehand tidak dengan meluruskan lengan sepenuhnya, 2) mahasiswa belum paham cara memegang raket pada saat melakukan pukulan smash forehandpermainan bulutangkis, 3) mahasiswa belum percaya diri pada saat melakukan gerakan pukulan smash forehandpermainan bulutangkis.Kegiatan siklus II yang direalisasikan melalui pembelajaran lempar bola atas memberikan hasil sebagai berikut: 1) mahasiswa mulai memahami konsep dasar pukulan smash forehand permainan bulutangkis, pemahaman ini dapat dilihat dari cara mahasiswa melakukan dan mempelajari gerakan pukulan smash forehandpermainan bulutangkis dengan baik, 2) mahasiswa dapat melakukan tahapan-tahapan pukulan smash forehandbulutangkis dengan baik, 3) motivasi dan percaya diri mahasiswa meningkat pada saat melakukan pukulan smash forehandpermainan bulutangkis. Hasil penelitian ini adanya peningkatan hasil belajar smash forehandbulutangkis melalui pembelajaran lempar bola atas, peningkatan terjadi disetiap pembelajaran yang dimulai dengan observasi awal, siklus I dan diakhiri pada siklus II. Terjadi peningkatan pada aspek psikomotor, mahasiswa telah memahami konsep gerak smashforehandbulutangkis. Pada aspek kognitif, pemahaman mahasiswa bertambah seiring dengan proses mengikuti pelajaran, terlihat dari semangat dan antusias mahasiswa mengikuti pembelajaran, kepercayaan diri mahasiswa dalam berinteraksi dengan mahasiswa dan dosen, nilai kejujuran, kedisiplinan, kerjasama tanggung jawab dan toleransi antar mahasiswa yang mereka tunjukkan. Kata kunci : Modifikasi, latihan forhand dan back hand , Media Pembelajaran Bulutangkis.